2018
DOI: 10.3390/app8020158
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Xanthine Oxidase Inhibitors from Clerodendranthus spicatus with Xanthine Oxidase Immobilized Silica Coated Fe3O4 Nanoparticles

Abstract: Abstract:In this study, xanthine oxidase immobilized silica coated Fe 3 O 4 nanoparticles (Fe 3 O 4 @SiO 2 -XO) were successfully prepared and characterized by transmission electron microscope, X-ray powder diffraction, Fourier transform infrared spectroscopy and vibrating sample magnetometer. The average diameter of the Fe 3 O 4 nanoparticles was about 300 nm to 350 nm with a shell thickness of 60 nm. The maximum saturation magnetization of the Fe 3 O 4 @SiO 2 -XO nanoparticles was 44.9 emu/g, which ensured t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Liu et al. (2018) isolated two compounds from extract of Clerodendranthus spicatus using XO‐immobilized silica‐coated Fe 3 O 4 nanoparticles and identified them as gardenin B and eupatorin (seen in Figure 2). Both of them possessed multiple methoxyl groups and showed potent XO inhibitory effects in vitro with IC 50 values of 1.488 and 11.197 μg/mL, respectively.…”
Section: Flavonoidsmentioning
confidence: 99%
See 2 more Smart Citations
“…Liu et al. (2018) isolated two compounds from extract of Clerodendranthus spicatus using XO‐immobilized silica‐coated Fe 3 O 4 nanoparticles and identified them as gardenin B and eupatorin (seen in Figure 2). Both of them possessed multiple methoxyl groups and showed potent XO inhibitory effects in vitro with IC 50 values of 1.488 and 11.197 μg/mL, respectively.…”
Section: Flavonoidsmentioning
confidence: 99%
“…Liu et al. screened four XO inhibitors from Puerariae flos extract with centrifugal ultrafiltration coupled with HPLC‐MS, which were identified as tectoridin, daidzin, ononin, and biochanin A (Liu et al., 2018). Another three isoflavonoids, 2′‐hydroxygenistein, 3′‐methoxygenistein, and lupinalbin A, were isolated from the ethyl acetate fraction of Apios americana on the catalytic reaction mediated by XO (Kim & Jin, 2019).…”
Section: Flavonoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gnetum parvifolium was extracted by microwave-assisted extraction method [23]. Twenty grams of samples were transferred into a conical flask containing 200 mL of 90% ethanol solution.…”
Section: Methodsmentioning
confidence: 99%
“…spicatus possesses diverse bioactive properties involving antioxidant, , anticancer, antiobesity, , anti-inflammatory, , diuretic, and nephroprotective ,,, effects. Nevertheless, according to a literature survey, there has been no report to pinpoint the secondary metabolites that might be responsible for anti-gouty properties of this plant. , We evaluated the effects of ethanol extract (EE) and its subfractions of C. spicatus on the treatment of gout, and the results showed that the ethyl acetate fraction (EAF) had potent anti-gouty arthritis, analgesic, and antihyperuricemic activities.…”
Section: Introductionmentioning
confidence: 99%